The folk etymologies of toponyms in “Legendy i podania Kurpiów” - Rogowska-Cybulska, Ewa (Papers in Linguistics, 2019)
The article presents the folk etymologies of names of villages and cities, which are contained in book “Legendy i podania Kurpiów” (selection and editing I. Choroszewska-Zyśk, M. Samsel, M. Grzyb, Ostrołęka 2008), especially the names of villages and cities situated in Kurpie and near Kurpie: Chudek, Dobry Las, Jazgarka, Jednorożec, Mały Płock, Ostrołęka, Serafin, Szwed, Tatary, Wykrot and Zbójna. The author juxtaposes all the folk etymologies of these names and compares them structurally and semantically with their scientific etymologies.